Beyond Self-Rated Health: The Adolescent Girl's Lived Experience of Health in Sweden. (February 2013) - Larsson, Margaretha; Sundler, Annelie Johansson; Ekebergh, Margaretha
The aim of this phenomenological study was to describe the phenomenon of health as experienced by adolescent girls in Sweden. Fifteen adolescent girls were interviewed with a focus on what made them feel well in their everyday life. This study reveals that the adolescent girl's health is a complex phenomenon interwoven with their lives. Health arises in meaningful contexts, in an adolescent girl's relations to others as well as in her ability to manage her life. Health is shaped in their everyday life and can be understood as a mood of "being" well that involves actions and practices. The results show that it is important to meet these girls from an open approach in order to support and strengthen their health and well-being. The health of adolescent girls can be supported, and it is a challenge for professionals, particularly school nurses, who meet these girls in everyday life to improve their health.